High-intensity gait training in subacute stroke resulted in increased discharge home from inpatient rehabilitation: a quality improvement study - Britton-Carpenter, Amanda; Thomas, Jade; Billinger, Sandra A. (Frontiers in Stroke, 2025)
BackgroundHigh-intensity gait training (HIGT) has emerged as a promising intervention to improve walking outcomes post-stroke. This quality improvement project aimed to increase the intensity of gait training for patients post-stroke in inpatient rehabilitation and evaluate HIGT's effects on functional mobility and discharge outcomes.MethodsEighty-four patients post-stroke admitted to inpatient rehabilitation (2019–2021) were divided into HIGT (n = 32) and standard of care (SoC; n = 52) groups. Baseline characteristics were compared using t-tests or χ2 tests. Linear mixed-effects models evaluated changes in Inpatient Rehabilitation Facility Patient Assessment Instrument (IRF-PAI) (total and item-level) and secondary outcomes (6-min walk test (6 MWT), 10-Meter Walk Test (10 MWT), berg balance scale (BBS), Functional Gait Assessment, Five Times Sit to Stand Test, and Activities-Specific Balance Confidence Scale). Logistic regression examined predictors of discharge destination.ResultsGroups were similar at baseline except for length of stay, which was longer for HIGT (16.6 vs. 11.1 days; p < 0.01). IRF-PAI Mobility improved significantly across all patients (p < 0.001), with a significant time × group interaction (p = 0.035) favoring HIGT. Item-level differences favored HIGT for “Chair/Bed-to-Chair Transfer” (p = 0.007), “Sit to Stand” (p = 0.005), and “Walk 10 Feet” (p = 0.008). Secondary outcomes improved within groups (p < 0.05) but did not differ significantly between groups. HIGT participants were more likely to discharge home (adjusted OR = 8.0, 95% CI [2.26–39.1], p = 0.003).ConclusionPatients receiving HIGT demonstrated greater functional mobility gains and were more likely to discharge home than those receiving standard care. HIGT may enhance post-stroke recovery and support independent living. Further research should assess fidelity, long-term outcomes, and broader implementation.